2017
DOI: 10.1002/jtr.2147
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and poverty alleviation: An empirical analysis using panel data on Peru's departments

Abstract: This paper analyses the impact of tourism on total and extreme monetary poverty, in order to illuminate the debate surrounding the links between tourism and poverty. We apply fixed effects models to panel data on the Peruvian departments for the period 2001–2013. We also identify the key factors in the tourism model affecting the empirical results. Our findings show that tourism is important for the poor, but its benefits do not reach the extreme poor to the same extent, and its potential is not fully exploite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 45 publications
1
11
0
3
Order By: Relevance
“…To assist in controlling for omitted variable bias, the current study performs the fixed regression. Because of its robustness, the fixed regression has been frequently used by both governance (e.g., V. Z. Chen, Li, & Shapiro, ; Prommin, Jumreornvong, & Jiraporn, ; Schultz et al, ) and tourism researchers (e.g., Demir & Gozgor, ; Llorca‐Rodriguez, Casas‐Jurado, & García‐Fernández, ; Saha & Yap, ) to tackle the issue of omitted variable bias. The second bias is an endogeneity, which is the issue of simultaneous causation between variables (Agrawal & Knoeber, ; Campbell & Minguez‐Vera, ; C. M. Yeh & Trejos, ).…”
Section: Methodsmentioning
confidence: 99%
“…To assist in controlling for omitted variable bias, the current study performs the fixed regression. Because of its robustness, the fixed regression has been frequently used by both governance (e.g., V. Z. Chen, Li, & Shapiro, ; Prommin, Jumreornvong, & Jiraporn, ; Schultz et al, ) and tourism researchers (e.g., Demir & Gozgor, ; Llorca‐Rodriguez, Casas‐Jurado, & García‐Fernández, ; Saha & Yap, ) to tackle the issue of omitted variable bias. The second bias is an endogeneity, which is the issue of simultaneous causation between variables (Agrawal & Knoeber, ; Campbell & Minguez‐Vera, ; C. M. Yeh & Trejos, ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, addressing local community participation in tourism development, with an appropriate approach toward community empowerment, plays a crucial role in poverty alleviation (Ndivo and Cantoni 2016). Llorca-Rodríguez, Casas-Jurado, and García-Fernández (2017) researched tourism impact on total and extreme monetary poverty and found that low levels of community involvement in Peru prevented “tourism potential from being fully exploited” (p. 8).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Por el contrario, otros recalcan que el desarrollo turístico en los destinos emergentes tiende justamente a un continuado empobrecimiento de la población (Gascón, 2015;Scheyvens & Rusell, 2012). Asimismo, otros trabajos sugieren la no existencia de una clara relación de causalidad entre el crecimiento del sector turístico y el nivel de desarrollo socioeconómico en este tipo de destinos (Llorca-Rodríguez et al, 2017;Mahadevan et al, 2017).…”
Section: Revisión De Literaturaunclassified
“…xico, Francia o Italia, entre otros (Shahzad et al, 2017). Otros, en cambio, niegan la existencia de esa causalidad asociada al turismo (Llorca-Rodríguez et al, 2017;Mahadevan et al, 2017).…”
Section: Causalidad Del Binomio Turismo-desarrollo Económicounclassified